Eutectic Electrolyte with Unique Solvation Structure for High‐Performance Zinc‐Ion Batteries. (15th June 2022) - Geng, Lishan; Meng, Jiashen; Wang, Xuanpeng; Han, Chunhua; Han, Kang; Xiao, Zhitong; Huang, Meng; Xu, Peng; Zhang, Lei; Zhou, Liang; Mai, Liqiang
Abstract: Zinc‐ion batteries (ZIB) present great potential in energy storage due to low cost and high safety. However, the poor stability, dendrite growth, and narrow electrochemical window limit their practical application. Herein, we develop a new eutectic electrolyte consisting of ethylene glycol (EG) and ZnCl2 for dendrite‐free and long‐lifespan ZIBs. The EG molecules participate in the Zn 2+ solvation via coordination and hydrogen‐bond interactions. Optimizing the ZnCl2 /EG molar ratio (1 : 4) can strengthen intermolecular interactions to form [ZnCl(EG)] + and [ZnCl(EG)2 ] + cations. The dissociation–reduction of these complex cations enables the formation of a Cl‐rich organic–inorganic hybrid solid electrolyte interphase film on a Zn anode, realizing highly reversible Zn plating/stripping with long‐term stability of ≈3200 h. Furthermore, the polyaniline||Zn cell manifests decent cycling performance with ≈78 % capacity retention after 10 000 cycles, and the assembled pouch cell demonstrates high safety and stable capacity. This work opens an avenue for developing eutectic electrolytes for high‐safety and practical ZIBs. Abstract : A brand new eutectic electrolyte consisting of ethylene glycol (EG) and ZnCl2 has a unique solvation structure and could enable the formation of a Cl‐rich organic–inorganic hybrid solid electrolyte interphase film on a Zn anode, realizing highly reversible Zn plating/stripping.